Analysis of the structure of Basic Health Units in Brazil to conduct telehealth actions: a comparison of two cross-sectional studies - Denise Oliveira Franco; Mauro Henrique Nogueira Guimarães Abreu; Rafaela Silveira Pinto; Antônio Thomaz Gonzaga Matta-Machado; Renata Castro Martins (BMC, 2024)
Abstract Background Telehealth uses Information and Communication Technologies (ICT) in distance health-related activities between professionals, managers, and patients of health services. This cross-sectional study compared the ICT infrastructure available in Brazilian Basic Health Units (BHU) for telehealth actions, along with evaluation cycles of the National Program for Improving Access and Quality of Primary Care (PMAQ-AB). Methods Data from the second and third cycles of the PMAQ-AB were used. A total of 22,021 BHUs were evaluated concerning the availability of computers, cameras, stereo boxes, microphones, printers, television, and internet available. The presence of each ICT equipment assigned a score to each BHU. The sum of these scores assigned a final score to the BHU and was used for comparison among different Brazilian regions. The data were analyzed descriptively and by Wilcoxon test (p ≤ 0.05) using SPSS v. 25. Results The increase in the median number of ICT equipment was statistically significant in the BHU in Brazil and the Brazilian regions (p < 0.001). The South, Southeast, and Midwest regions had the highest median scores in both cycles. Conclusions The availability of ICT equipment for telehealth actions in BHU improved over the PMAQ-AB cycles, with differences in the ICT structure between Brazilian regions.